The Muensterelloidea: phylogeny and character evolution of Mesozoic stem octopods. (28th June 2019) - Fuchs, Dirk; Iba, Yasuhiro; Heyng, Alexander; Iijima, Masaya; Klug, Christian; Larson, Neal L.; Schweigert, Günter
Abstract: The Muensterelloidea is a superfamily of teudopseid octobrachians with a posteriorly patella‐shaped gladius. A morphometric comparison based on 148 muensterelloid gladii has yielded five new species accommodated in three new genera: Engeseriteuthis arcuatus gen. et sp. nov., Muensterella jillae sp. nov., Muensterella spinosa sp. nov., Tyrionella fauseri gen. et sp. nov. and Muensterellina johnjagti gen. et sp. nov. Cretaceous taxa ' Tusoteuthis ' cobbani and ' Muensterella ' tonii are re‐combined and placed within the genus Enchoteuthis . We introduce categories for gladius proportions applicable for both muensterelloid and non‐muensterelloid octobrachian gladii. A 2D‐landmark analysis including 64 muensterelloid and non‐muensterelloid gladii statistically confirms that the Muensterelloidea possess the smallest median field sizes of all Mesozoic gladii. We consider the lateral field‐dominated 'gladius' of the family Patelloctopodidae ( Patelloctopus, Pearceiteuthis ) to be vestigial (i.e. shorter than the mantle length) suggesting that the Patelloctopodidae are the last shared ancestors of incirrate and cirrate octopods. According to a phylogenetic analysis based on 31 gladius characters, the Muensterelloidea mainly consists of the ' Muensterella ‐Enchoteuthidae' and the 'patelloctopodid' clade. Ancestral character state reconstructions suggest that an increasing posterior growth front is accompanied by a continuous decrease of the median field length. This milestone in the evolution of the octopod gladius vestige occurred between the Early and Middle Jurassic. The benthic life style of incirrate octopods (including Cretaceous palaeoctopodids) was adopted by Jurassic Patelloctopodidae, which arose from nectonic to nectobenthic teudopseid ancestors. There is currently no evidence to suggest a pelagic origin for benthic octopods.